Point of care testing – collaboration between a nurse and a laboratory laboratorians is needed - Wojnar, Anna; Sztefko, Krystyna (Nursing Problems / Problemy Pielęgniarstwa, 2018)
The point of care testing (POCT) technique denotes performing lab tests directly in the presence of a patient. A promptly obtained lab result facilitates a prompt therapeutic intervention. POCT is a very dynamically developing field of laboratory diagnostics and the equipment used while employing the technique is increasingly more common in various locations in hospitals, outpatient clinics, doctor’s offices and homes of the patients. The quality of patient care depends among others on the reliability of lab results. The equipment has to be used and maintained in keeping with the producer’s recommendations and be provided with a quality control system. Tests performed using the POCT method require proper documentation and the operators of the equipment should be properly educated and present a high level of knowledge and skills. The objective of the paper is drawing attention to the important role of the nurse in obtaining reliable POCT results and to the necessary collaboration between the nurses and laboratory diagnosticians.